Groundwater Vulnerability Assessment Using Multivariate Statistical Analysis and GIS in the Foothills of Western Himalayan State, India - Sharma, Pravidhi; Aggarwal, R. K.; Walia, Kashish; Mehta, Gagan; Kumar, Jatin (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during July, 2019 to July, 2020 at industrial region of Solan district, Himachal Pradesh, India to study the groundwater quality status. Water quality parameters such as pH, EC, Turbidity, TDS, Ca2+, Cl-, NO3-, BOD, COD, and heavy metals (Fe, Pb, Cr, Cu, Mn) were analyzed and WQI (Water Quality Index) was computed. Thereafter, Arc GIS software was used for the spatial distribution of these parameters to locate the regions with the best drinking water quality within the study area. The results of the study revealed that except for the concentration of BOD and heavy metals such as Fe, Pb, Cr, and Cu, which exceeded the acceptable limits in some places, all of the examined parameters were well below desirable limits as per the Bureau of Indian Standards (BIS) and WHO for drinking and domestic purposes. Furthermore, a correlation matrix and PCA were subsequently formulated and examined using R software and SPSS respectively to determine the most significant parameters contributing to groundwater pollution. The WQI values indicated that only 13.3% of the groundwater sample falls in the good water category, the rest 60% falls in the poor category and 26.7% falls in the very poor category in both seasons. The findings of the present study therefore implied that groundwater of the region was under deteriorating water quality particularly, in the central and north-western region of the watershed and requires proper treatment before consumption as well as protection from the perils of geogenic/anthropogenic contamination.